Ability of serum C-reactive protein and white blood cell cout in predicting acute schemic stroke. A short -term follow-up study - Babak Bakhshayesh-Eghbali; Seyed-Ali Roudbary; Seddigheh Basir-Jafari; Seyedeh-Parand Nabizadeh; Naghmeh Naderi-Asrami; Reza Sohrabnejad (Babol University of Medical Sciences, 2016)
Background: Stroke is one of the leading causes of mortality and long-term morbidity. The aim of the present study was to determine the ability of baseline serum C-reactive protein (CRP) and white blood cell count (WBC) values in predicting the outcome of acute ischemic stroke (AIS). Methods: This study consisted of patients with first AIS referred to Poursina Hospital, Rasht, Iran. Severity of stroke was determined according to the National Institute of Health (NIH) Stroke Scale at the time of admission. Serum CRP levels and WBC count were measured at the time of admission. All patients were followed-up for 90 days after discharge and the severity of stroke was assessed using modified Rankin Scale. Receiver operating characteristic curve analysis was used for calculating the most appropriate cutoff point of CRP and WBC count for differentiating patients with and without poor outcome at the end of the study period. Results: A total of 53 out of 102 patients (52%) had poor outcome. The most appropriate cutoff value for CRP in differentiating patients with and without poor outcome was 8.5mg/l (sensitivity: 73.1%, specificity: 69.4%) and for WBC the difference did not reach to a significant level. The cutoff points of CRP > 10.5 mg/ml yielded a predictive ability at sensitivity: 75%, specificity: 63.8% whereas predictive ability of WBC for mortality was at a borderline level. Conclusion: These findings indicate that high levels of serum CRP in AIS at the time of admission is associated with poor prognosis. However, this study found no ability for WBC in predicting AIS outcome